Self-determination, Identity and International Relations - Barata, Maria João (2013)
In this paper, I argue that self-determination constitutes the selves by which it is claimed. I base this argument on a reflexivist conception of identity. The process, I suggest, goes like this. Human groups striving for political independence, autonomy, or a share in state power draw on the norm of self-determination to seek international support and recognition. This norm epitomizes general ideas of freedom, justice and the good life, but it also legitimizes (and illegitimates) concrete ways of bound and rule political communities. These ideas and rules enter the process by which the group construes as a self. They influence the thinking and acting of the group upon itself, and so get reflected in its constitution.